An Innovative Personnel For Pharmaceutical Administration - ., Luvkush (Asian Journal of Pharmaceutical Research and Development, 2023)
The drug-administration controls medication business. Its emergence as the effective controlling body in next century requires wise decisions for the realistic application of pharmaceutical quality; the professional foresight suggested that drug should coordinate with pharmacy academics for the specialized graduates in pharmacy administration